Ziarah Prihatin Ramadan-UMP Alumni extends help, brings cheers to Asnaf - Junaidi, Zakaria (2019)
In view of the festive celebration of Hari Raya Aidilfitri, and coupled with concerns about the plight of a number of afflicted families in the vicinity of Kuantan, Pahang, the Graduates Association at Universiti Malaysia Pahang (UMP), or fondly referred to as UMP Alumni, conducted a “Ziarah Prihatin Ramadan” programme to extend a helping hand and bring cheers and joy to the needy.